The space paradox in graphic representation - Lange-Küttner, Christiane; Vinueza Chavez, Ximena (Frontiers in Psychology, 2022)
The negative space drawing technique refers to drawing the transparent space around and between the objects, rather than drawing the objects themselves. This space-based instruction is thought to attenuate object-specific visual attention and to enhance perception of a spatial expanse. Developmentally, it is equivalent to the Piagetian dichotomic space concept of filled and empty space. A sample of 96 children from 5 to 12 years of age and 24 adults (N=120) drew on a computer tablet a real-life model spacebox placed in front of the participant, with three cubes placed inside the model. Children followed two instructions, a Visual Realism (VR) Instruction ‘Please draw the three cubes and the box as you can see them’ and a Negative Space (NSp) Instruction ‘Please draw the space around the objects’, with the sequence counterbalanced. NSp outline drawings began to show from 9 years onwards. A positive effect of the NSp technique showed for occlusion drawing because of the depiction of common contour of objects which could create a cohesive scene feature such as a horizon. The VR instruction focused attention towards the space box and enhanced 3D drawing of both the spacebox and the cubes. Thus, it could be concluded - rather paradoxically - that drawing in 3D is better based on object- than on space-based attention, while drawing occlusion is better based on space-based than object-based attention. We suggest, however, that a better definition of VR as attention to object appearances is that VR unifies objects and spatial context into one global plane.